Redescription of Juticus furcidens Roewer, 1943 (Opiliones: Gonyleptidae), with a discussion of its relationships in the subfamily Gonyleptinae - Hara, Marcos R.; Pinto-Da-Rocha, Ricardo; Benedetti, Alípio R. (Zootaxa, 2018)
As part of an ongoing revision of the largest gonyleptid subfamily, Pachylinae, we examined Juticus furcidens Roewer, 1943. This is an elusive species mentioned only in catalogues after its description. In this paper, we redescribe it according to modern standards, including its male genitalia for the first time, which exhibit typical features of the gonyleptid K92 clade. Considering also other features from the body and appendages, we transfer J. furcidens to Gonyleptinae, and we discuss its relationships with other Gonyleptinae sensu stricto. In addition, we present a new record besides those of the type material, clarifying the hitherto imprecise distribution.